115 The Impact of Smoking on Mortality Following Percutaneous Coronary Intervention-an Observational Study. (6th June 2015) - Parasuraman, Sathish Kumar; Zaman, Afzar; Broadhurst, Paul; Egred, Mohaned; Ahmed, Javed; Garg, Deepak; Bagnall, Alan; Noman, Awsan; Das, Rajiv
Abstract : Aim: To assess the impact of smoking on mortality following percutaneous coronary intervention (PCI). Methods: A total of 13041 patients underwent PCI between 2008 and 2011 at two large tertiary centres. Data on smoking status were missing in 385 patients. The remaining 12656 patients were included in this analysis. Patients were divided into three groups according to their smoking status at the time of index PCI procedure: non- smokers (n = 4288, 33.9%), ex-smokers (n = 4806, 38.0%) and current smokers (n = 3562, 28.1%). Results: Current smokers underwent PCI at a younger age (mean ± SD) and more frequently for acute coronary syndrome (ACS) (57 ± 11 years, 84.1% for ACS) compared to non-smokers (67 ± 12 years, 62.9%) and ex-smokers (67 ± 11 years, 57.0%), p < 0.0001 for both. Overall 30-day mortality rate was (1.8%). In a logistic regression model adjusted for several confounders, the adjusted odds ratios (95% confidence intervals [CI]) for 30-day mortality were 0.98 (0.70–1.38) in ex-smokers and 1.60 (1.10–2.32) in current smokers compared to non-smokers. Overall mortality rate between 30 days and 6 months post PCI was 1.5%. In the multiple Cox proportional hazards model, the adjusted hazard ratios (95% CI) for mortality between 30 days and 6 months were 1.19 (0.84–1.67) in ex-smokers and 1.03 (0.65–1.65) in current smokers compared to non-smokers. Conclusions: This large observational study of unselected, real-world patients demonstrates a younger age at presentation for PCI and increased 30-day post-PCI mortality in current smokers compared to ex-smokers and non-smokers. Ex-smokers have a similar age at presentation and post PCI mortality outcome as non-smokers. These findings further re-enforce the public health message regarding the harmful effect of smoking and the benefits of smoking cessation in patients undergoing PCI.